Criminal Code Policy in The Effort of Corruption Prevention in Institutions Regional Disaster Management Agency - Masyhadi Irfani; Ira Alia Maerani (Jurnal Daulat Hukum, 2019)
Settings on the Crime of corruption in the procurement of goods and services defined in the Criminal Code as well as in Act Corruption today. However, there are still weaknesses contained in the Anti-Corruption Act today, one about the formulation of minimum criminal sanctions, which do not formulate sentencing guidelines to implement this minimum criminal threats.Corruption that has grown and occurs systemically and widespread must be done explicitly countermeasures to combat it. Corruption need severe sanctions (the imposition of the death penalty if necessary) in addition to confiscation of the wealth gained from corruption. Cooperation of various parties must be improved so that the law enforcement process runs with orderly and appropriate procedures, so that the perpetrators of criminal sanctions in kind (so that these sanctions have a deterrent effect) and eventually become a member of the public good and useful.Some issues regarding the criminal system that it is still in need of repair in the future is to be considered in order to create legislation that is even better. In 2018 the concept of the Criminal Code has been no formulation of the articles related to the criminal system that specifically regulates the crime of corruption by local officials, only qualifying offense of corruption that meet the elements of the subject that is a local official.Keywords: Legal Policy; Corruption.